THE EFFECT OF PROBLEM-BASED LEARNING MODEL USING PHET SIMULATION ON PHYSICS STUDENT’S ACHIEVEMENT - aisyah fadillah; Ratnawulan Ratnawulan; Silvi Yulia Sari; Renol Afrizon (PILLAR OF PHYSICS EDUCATION, 2023)
The purpose of this study is to determine the effect of a problem-based learning model supported by PhET media on student physics learning results. This research conducted at Senior High School 6 PadangThe type of study conducted was a design of quasi-experimental. The study design used was a posttest-only control design. Samples were selected from Class X IPA Senior High School Number 6 Padang, the study population for the 2021/2022 school year, using a targeted technique of sampling. XI IPA 1 class as the experimental class and XI IPA 2 as the control class. The data collection instrument used is a test instrument. The analysis of data techniques used are descriptive statistical analysis the tes are, normality, homogeneity, and U test (Mann-Whitney). From the research data analysis, the experimental class's average value was 80.69, higher than the control class, 62.14. The results of hypothesis testing obtained zcount = 7.24 and ztabel = 1.96 by the Ho rejection criteria, namely, reject Ho if zcount <-ztabel or zcount>ztabel. The conclusion that the effect of learning problem-based model in static fluid learning using LKPD Based on PhET on physics learning results at Senior High School number 6 Padang.